Performance of front line demonstrations on yield and economics of greengram in Kachchh District of Gujarat - Traloki Singh; Arvind Singh Tetarwal; Rahul Dev; Pankaj Nautiyal (Annals of Agricultural Research, 2024)
Greengram is one of the important crops among the pulses. This crop holds the key to increase the income of the farmers and to achieve self-sufficiency in pulse production. A total 48 Frontline demonstrations on greengram were carried out by the ICAR-CAZRI, Krishi Vigyan Kendra (KVK), Bhuj (Kachchh-II) at farm ers field in 19.2 ha area during kharif, 2016-20 to study the performance of frontline demonstrations (FLDs) on yield and economics of green gram in Kachchh region with improved variety GM 5. The result of the FLDs conducted by KVK shows a better impact on farmer’s livelihood due to significant increase in yield (961.3 kg ha-1) over local check (772.7 kg ha-1) with average 24.54% increased yield. The technology gap ranged between 218 kg to 270 kg ha-1 and the extension gap trend of ranged between 166 to 202 kg ha-1. The economics of FLDs revealed the viability of enhanced technology with a net return of Rs.61960 ha-1 and a benefit-cost ratio (BCR) of 2.95 compared to Rs. 40814 ha-1 and 2.61 in farmer’s practice. A wide range of technology gaps and extension gaps had a detrimental influence on yield output and net return. The results revealed that the adoption of high yielding variety with full package of practices increased greengram productivity with a significant reduction in extension and technology gap.